Editorial Preface - Ismail, Al Emran; Daud, Zawawi; Ibrahim, Nabilah (International Journal of Integrated Engineering, 2018)
This is the first volume of year 2018 which contained of three main engineering fields such as Mechanical and Manufacturing, Civil and Environmental and Electrical and Electronic Engineering. In this volume there are 30 number of papers published and indexed mainly in SCOPUS, GOOGLE SCHOLAR and Malaysia Citation Centre (MCC). It is about 30% of these papers came from international authors and the number is growing. Editorial board and the Penerbit UTHM would like to express their appreciation to national and international authors who have contributed their work to the world of knowledge. Lastly, we would also like to thank all reviewers who make the supportive reviews, comments and suggestions in order to enhance the quality of this journal. In order to access the online version of this issue along with archived editions please visit our website http://penerbit.uthm.edu.my/ojs/index.php/ijie/.